Prototype for Digitizing the Sato Kewan Fairy Tale as A Javanese Language Education Media - Indri Meilani; Eka Yuli Astuti (Jurnal Paedagogy, 2024)
This research aims to develop and validate the digitalization product of the Sato Kewan fairy tale as a Javanese language educational medium for elementary school students. This research uses the development method (Research and Development) with the ADDIE model to design a learning system. This development model goes through five steps: Analysis, Design, Development, Implementation, and Evaluation. The validation questionnaire for linguists and media experts is a research instrument. Data analysis techniques include qualitative and quantitative descriptive analysis. Based on data from validity results by linguists and media experts on the stop motion animation video of Sato Kewan's fairy tale, the media is a suitable criterion for use. For the language aspect, the language expert scored 75%, and the content aspect was 80%. The visual aspect got 75%, the audio aspect 83%, and 83% effectiveness.